2018
DOI: 10.1002/ejic.201701080
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Highly Fluorescent Carbon Dots from Spinach and Multipurpose Applications

Abstract: Highly fluorescent carbon dots (CDs) have been prepared from natural spinach by a hydrothermal method. In this work, we have demonstrated that the CDs have a high quantum yield of 53 %, and exhibit special responses to 2-nitrophenol (2-NP) and 4-nitrophenol (4-NP). Solutions of the CDs showed clear fluorescence quenching in the presence of 2-NP and 4-NP; the detection limits of 2-NP and 4-NP were 1.06 and 0.50 μM,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The limit of detection of Cr­(VI) and 4-NP by N-CDs­(II) and those reported in the literature for different types of carbon dots are presented in Table A and Table , respectively. It revealed that the probe developed by us, i.e., N-CDs­(II), is efficient for detecting Cr­(VI) and 4-NP. In addition, our method provides an option for detecting Cr­(VI) as CrO 4 2– .…”
Section: Resultsmentioning
confidence: 75%
“…The limit of detection of Cr­(VI) and 4-NP by N-CDs­(II) and those reported in the literature for different types of carbon dots are presented in Table A and Table , respectively. It revealed that the probe developed by us, i.e., N-CDs­(II), is efficient for detecting Cr­(VI) and 4-NP. In addition, our method provides an option for detecting Cr­(VI) as CrO 4 2– .…”
Section: Resultsmentioning
confidence: 75%
“…Different chemical precursors such as ethylenediaminetetraacetic acid (EDTA) (Ankireddy and Kim, 2018;Yang et al, 2020), citric acid (Fang et al, 2017) and reduced glutathione (Vaz et al, 2017), and ethylene glycol ) also have been used as the source to synthesize C-Dots. Wide applications of C-Dots in biomedical applications for instance drug delivery (D'souza et al, 2018), biosensing (Sarkar et al, 2018), bioimaging (Yang et al, 2014;Ren et al, 2018;Amjad et al, 2019) and gene transfer (Mohammadinejad et al, 2019), make it more suitable to move from chemical precursors to organic precursors. For example, numerous biomass has been used for the synthesis of C-Dots in recent years including papaya waste (Pooja et al, 2019), prawn shells (Gedda et al, 2016), grilled fish (Bi et al, 2017), Lycii Fructus (Sun et al, 2017), milk (Bajpai et al, 2019) fruit juices (Atchudan et al, 2018), etc.…”
Section: Green Synthesis Of Multifunctional C-dotsmentioning
confidence: 99%
“…As shown in Figure 9 a–c, strong emission peaks at 473 nm at 320 nm excitation wavelength were observed for p-NA by ZnWO 4 , NiWO 4 , and ZnNiWO 4 in a methanol environment, which suggested that p-NA was most comprehended by metal tungstate and mixed metal tungstate nanoparticles. This phenomenon could have been caused by the hydrogen bond and the strong radiative transitions between tungsten and oxygen within the (WO 6 ) 6− molecular complex [ 36 , 41 ]. The order of detection was found to be p-NA > 2-NP > m-NP > 4-NB.…”
Section: Resultsmentioning
confidence: 99%